Synthesis, Regulation and Degradation of Carotenoids Under Low Level UV-B Radiation in the Filamentous Cyanobacterium Chlorogloeopsis fritschii PCC 6912 - Llewellyn, Carole A.; Airs, Ruth L.; Farnham, Garry; Greig, Carolyn (Frontiers in Microbiology, 2020)
Carotenoids in cyanobacteria play an important role in protecting against and in repairing damage against low level UV-B radiation. Here we use transcriptomics and metabolomic HPLC pigment analysis to compare carotenoid pathway regulation in the filamentous cyanobacterium Chlorogloeopsis fritschii PCC 6912 exposed to white light and to white light supplemented with low level UV-B. Under UV-B changes in carotenoid transcription regulation were found associated with carotenogenesis (carotenoid synthesis), photoprotection and carotenoid cleavage. Transcriptional regulation was reflected in corresponding pigment signatures. All carotenogenesis pathway genes from geranylgeranyl-diphosphate to lycopene were upregulated. There were significant increases in expression of gene homologues (crtW, crtR, cruF and cruG) associated with routes to ketolation to produce significant increases in echinenone and canthaxanthin concentrations. There were gene homologues for four β-carotene-ketolases (crtO and crtW) present but only one crtW was upregulated. Putative genes encoding enzymes (CruF, CrtR and CruG ) for the conversion of -carotene to myxol 2’-methylpentoside were upregulated. The hydroxylation pathway to nostaxanthin via zeaxanthin and caloxanthin (gene homologues for CrtR and CrtG) were not upregulated, reflected in the unchanged corresponding pigment concentrations in zeaxathin, caloxanthin and nostaxanthin, Transcripts for the non-photochemical quenching related Orange-Carotenoid-Protein (OCP) and associated Fluoresence-Recovery-Protein (FRP) associated with photoprotection were upregulated, and one carotenoid binding Helical-Carotenoid-Protein (HCP) gene homologue was downregulated. Multiple copies of genes encoding putative apocarotenoid related carotenoid oxygenases responsible for carotenoid cleavage were identified, including an upregulated apo-β-carotenal-oxygenase gene homologous to a retinal producing enzyme. Our study provides holistic insight into the photoregulatory processes that modulate the synthesis, photoprotection and cleavage of carotenoids in cyanobacterial cells exposed to low level UV-B. This is important to understanding how regulation of metabolism responds to a changing environment and how metabolism can be modulated for biotechnological purposes.